The Role of Discourse Analysis in Planning Economic and Social Processes. Managing Social Conflicts - Lymar, A. (Поліграф-Сервіс, 2024)
Success in implementing economic and social development objectives largely depends on the degree of relevance of these objectives for the potential beneficiary, as well as on the ability to convey to him the importance and validity of the actions and proposals being taken. This is all the more important against the backdrop of the dominant ideas, stereotypes of perception and interpretation of any reforms and changes in life in modern society, as well as taking into account the unresolved problem of public trust. Every attempt to intervene throughout life, even for the purpose of improving it, causes internal contradictions and conflicts. In this regard, it would be logical to consider the features of ways to inform society about proposed reforms and changes in the light of a discursive analysis of their content and essence.
Keywords: discursive analysis; social conflicts; typology of conflict situations